Pro Android with Kotlin Developing Modern Mobile Apps - Späth, Peter (Apress, 2018)
Develop Android apps with Kotlin to create more elegant programs than the Java equivalent. This book covers the various aspects of a modern Android app that professionals are expected to encounter. There are chapters dealing with all the important aspects of the Android platform, including GUI design, file- and data-handling, coping with phone calls, multimedia apps, interaction with location and mapping services, monetizing apps, and much more. Pro Android with Kotlin is an invaluable source for developers wanting to build real-world state-of-the-art apps for modern Android devices. You will: Integrate activities, such as intents, services, toasts and more, into your Android apps Build UIs in Android using layouts, widgets, lists, menus, and action bars Deal with data in your Android apps using data persistence and cloud access Design for different Android devices Create multimedia apps in Android Secure, deploy, and monetize your Android apps.